(untitled) (Praxis Educativa, 2025)
This article focuses the educational policies of Milei’s Presidency. To this purpose, his positions are placed within the libertarian spectrum, and the characteristics of the ideological frameworks to which he adheres are presented: anarcho-capitalism and paleolibertarianism. Normative and journalistic articles are taken as units of analysis. The design of this research includes qualitative techniques among which the content analysis of normative and journalistic sources stands out. This study foresees different scales of analysis since it is necessary to contemplate the federal form of the Argentine State in order to understand sectoral policies. Likewise, the normative framework currently in force in the country regarding the right to education is taken into account. Finally, educational policies are discussed and, in particular, the National Literacy Plan and the questioning of Comprehensive Sexual Education are analyzed in order to account for the ongoing libertarian recomposition.